Quality seeds wanted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Seed Policy and Programmes for Sub-Saharan Africa. FAO Plant Production and Protection Papers. 1999. 244 pp. ISBN 925104323 X US$ 26 E 28.65 FAO Sales and Marketing Group Viale delle Terme di Caracalla 00100 Rome, Italy Fax: +39 06 57 05 33